Neutrophil-activating protein in Bacillus spores inhibits casein allergy via TLR2 signaling - Liang, Zhuwei; Zhang, Chao; Liu, Xiaoyu; Yang, Kaiyue; Xiong, Zhile; Liang, Bingshao; Mai, Jialiang; Xiao, Xiaojun; Liu, Jie; Yang, Pingchang; Xu, Damo; Zhou, Zhenwen (Frontiers in Immunology, 2024)
Background Milk allergy commonly occurs in children, mainly caused by bovine-derived casein (CAS) protein. Neutrophil-activating protein (NAP) of Helicobacter pylori plays an immunomodulatory role with potential to suppress Th2-type immune responses. Bacillus subtilis (B. subtilis) spores are commonly used as oral vectors for drug delivery. Objective To investigate whether recombinantly expressed NAP on B. subtilis spores could be an effective treatment for CAS allergy in mouse. Methods After CAS sensitization, mice were orally administered B. subtilis spores expressing recombinant NAP for 6 weeks. Allergic symptoms and parameters were evaluated after CAS challenge oral gavage, including allergic inflammation, splenic cytokines, and serum-specific antibodies. Protein levels of Toll-like receptor 2 (TLR2) and c-JUN in the jejunum tissue were measured by western blot. Bone marrow-derived macrophages (BMDMs) were stimulated with inactivated NAP spores to measure the influence on cytokine profiles in vitro. Results NAP recombinant spore treatment significantly reduced allergic symptoms and intestinal inflammation. Interleukin-12 and interferon-gamma levels increased, whereas serum CAS-specific IgG1 and IgE levels decreased. TLR2 and c-JUN expression levels were elevated in the jejunal tissue. Inactivated NAP spores polarized BMDMs to the M1 phenotype and enhanced cytokine expression, which were inhibited by a TLR2 neutralizing antibody. Conclusion NAP offers a new strategy in the treatment of CAS allergy by inhibiting the Th2 response, while eliciting macrophages to promote Th1 immune responses.